Studi Kepustakaan Pengaruh Suplementasi Madu dalam Pengencer Terhadap Kualitas Semen Ayam - Yosefina T. Sukanto; Nancy D. F. K. Foeh; Tarsisius Tophianong (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Honey is a thick, sweet-tasting liquid containing about 70-80% natural sugars, minerals, vitamins and enzymes. The content of 65% sugar is in the form of simple monosaccharides (fructose, glucose and sucrose). The high sugar content in honey can be used as a source of nutrients besides honey also acts as an antioxidant. This study aims to determine the antioxidants and other active substances in honey so that their addition to the diluent can maintain the quality of chicken semen during storage. This literature study was carried out through searching and collecting various literatures using Google Schoolar and PubMed then arranged using Mendeley. Sources of literature are scientific journals, scientific articles, Ebooks and seminar proceedings with